KONSEP MASLAHAT AT-THUFY DAN PENERAPANNYA DALAM KASUS KEWARISAN DI INDONESIA - Mayyadah Mayyadah (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
The terminology of maslahat belongs to at-Thufy is actually no different from the understanding of other Ushuliyyun thought. But in contrast to the majority of jurisprudents who became their predecessors, at-Thufy is known as a thinker who gives a greater portion of reason (logic thinking) in carrying out maslahat. This is illustrated by the basic principles of the concept of maslahat at-Thufy. One of them is that if there is a conflict between nas with maslahat, then the maslahat takes precedence over the nas. The concept of Maslahat at-Thufy has possibility of being able to be an inspiration for solutions to inheritance cases in Indonesia.